The Dynamics of the Antifascist Movement in the Context of Illiberal Democracy in Poland - Piotrowski, Grzegorz; Kocyba, Piotr (PARTECIPAZIONE E CONFLITTO, 2024)
The context of illiberal democracy since 2015 has re-designed the scene of Polish social movements, as Poland witnessed a democratic backslide. This has prompted a number of reactions, using either new or established forms of political resistance. The antifascist movement is one example of this shift. The former subcultural form of organized antifascist activism had to face new challenges – in particular, the institutionalization and normalization of xenophobic rhetoric and a growth of the far-right sector. This explores the role of changes in political and discursive opportunity structures for the reinvigoration of the antifascist movement in Poland, its (de)radicalization in some of its sectors, and changes in its priorities. Empirically, the paper is based on long-term qualitative research on the Polish antifascist movement as well as on the results of a protest survey conducted at the Warsaw Antifascist Street Party in 2021.